Pengembangan Mobile Learning Berbantuan Marvel App pada Pembelajaran Matematika Sekolah Dasar: Penelitian - Achmad Galih An Naufal; Rahmad Setyo Jadmiko; Aditya Pringga Satria (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research addresses the insufficient integration of technology in the use of learning media, where many teachers still depend on traditional media such as textbooks, worksheets (LKS), and conventional teaching methods. The goal of this study is to develop Mobile Learning media supported by Marvel App for fifth-grade Mathematics instruction and to evaluate its validity and applicability in the learning process. The research follows the ADDIE development model, comprising five stages: Analysis, Design, Development, Implementation, and Evaluation. Data was gathered through questionnaires and documentation. The research subjects included 1 media expert, 1 material expert, 1 linguist, 25 fifth-grade students, and the fifth-grade teacher at SD Negeri 1 Panggungrejo. The results revealed that the validity of the Mobile Learning media, supported by Marvel App for fifth-grade Mathematics, received scores of 96% from media experts, 96% from material experts, and 90% from linguists. Additionally, the applicability assessment from student questionnaires reached 89%, and the teacher's rating was 97%. Based on these findings, it can be concluded that the development of Mobile Learning media with Marvel App support in fifth-grade Mathematics instruction at SD Negeri 1 Panggungrejo is both valid and applicable, contributing to more engaging learning experiences.